1990
DOI: 10.1029/jc095ic03p02857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea maturity on satellite altimeter measurements

Abstract: For equilibrium arid near-equilibrium sea states, the Wave.slope variance is a function of wind speed U and of the sea maturity. The influence of both factors on the altimeter measurements of wind speed, wave height, and radar cross section cr ø is studied experimentally. The necessary theoretical background, both on wave statistics and on the near-nadir radar backscatter, is outlined. It is based on a recently proposed view that the effective fractal dimension for a surface patch corresponding to the equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 20 publications
2
43
0
Order By: Relevance
“…The first classification of wave types was proposed, and it was shown that the backscattered radar cross section during nadir sounding (radio altimeter) and consequently the retrieved wind speed depend on the type of waves. Accounting for this effect in the algorithm made it possible to increase the accuracy of wind speed retrieval from the Geosat radio-altimeter data (Glazman and Pilorz, 1990).…”
Section: Stydying Seas and Oceans From Spacementioning
confidence: 99%
“…The first classification of wave types was proposed, and it was shown that the backscattered radar cross section during nadir sounding (radio altimeter) and consequently the retrieved wind speed depend on the type of waves. Accounting for this effect in the algorithm made it possible to increase the accuracy of wind speed retrieval from the Geosat radio-altimeter data (Glazman and Pilorz, 1990).…”
Section: Stydying Seas and Oceans From Spacementioning
confidence: 99%
“…Such an equilibrium depends on the wind strength. When the wind stops blowing, the short waves decrease quickly, while the long waves propagate far from their source (and, in this case, are usually referred to as swell [18]). Accordingly, long waves are generated by strong far winds, at variance of short waves, which are generated by local winds.…”
Section: Concepts Of Ocean Modelingmentioning
confidence: 99%
“…They depend on the far wind intensity and direction and on the fetch area [18]. The algorithm for the long wave generation is detailed in [25].…”
Section: B Ocean Surface Descriptionmentioning
confidence: 99%
“…In uence of the wind-speed variability Figure 4 (b) and (c) can be related reasonably to the cases of Geosat and TOPEX/ Poseidon, respectively. Fortunately, it was possible to nd some previous studies by Glazman and Pilorz (1990), Ebuchi et al (1992 ) and Gower (1996), who performed qualitative or quantitative analyses of the impacts of window sizes on the comparison results using real Geosat and TOPEX/Poseidon altimeter data in conjunction with the US, Japanese and Canadian buoy data. These give an opportunity to check the validity and applicability of the present simulation results.…”
Section: In Uence Of the Altimeter Noise Levelmentioning
confidence: 98%
“…Their conclusions, however, are somewhat divided. One argument suggests that the variations of space and time windows do not have a crucial impact on the accuracy of satellite/buoy comparisons (Dobson et al 1987, Glazman andPilorz 1990). In contrast, another argument suggests that reducing the spatial lag persistently improves the agreement of windspeed measurements from altimeters and ocean buoys, while time lags of up to 1 h do not produce signi cant changes in the key statistics, such as the root mean square (RMS) diOE erence and the correlation coe cients (Gower 1996, Hwang et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%